2022
DOI: 10.14309/ajg.0000000000002149
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biologics on the Risk of Advanced-Stage Inflammatory Bowel Disease-Associated Intestinal Cancer: A Nationwide Study

Abstract: INTRODUCTION:The aim of this study was to evaluate the effect of biologics on the risk of advanced-stage inflammatory bowel disease (IBD)-associated intestinal cancer from a nationwide multicenter data set.METHODS:The medical records of patients with Crohn's disease (CD) and ulcerative colitis (UC) diagnosed with IBD-associated intestinal neoplasia (dysplasia or cancer) from 1983 to 2020 were included in this study. Therapeutic agents were classified into 3 types: biologics, 5-aminosalicylic acid, and immunomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…We believe that, altogether, these improvements are responsible for the reduction in excess cancer. Consistent with the broader trend of diminished CRC risk, published data on cancer stage at the time of diagnosis, although indirect, point to a reduction in advanced-stage cancer diagnosis in more recent cohorts [35]. In line with this, our study found that only 2 out of 28 malignancies included in some form of surveillance were diagnosed at advanced (III-IV) stage.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We believe that, altogether, these improvements are responsible for the reduction in excess cancer. Consistent with the broader trend of diminished CRC risk, published data on cancer stage at the time of diagnosis, although indirect, point to a reduction in advanced-stage cancer diagnosis in more recent cohorts [35]. In line with this, our study found that only 2 out of 28 malignancies included in some form of surveillance were diagnosed at advanced (III-IV) stage.…”
Section: Discussionsupporting
confidence: 90%
“…The safety profile of these treatments is now well established and their risk of malignancy reassuring. Interestingly, a recent Japanese nationwide study including over a thousand IBD-associated cancers found that use of biologics was associated with earlier-stage, rather than advanced-stage, cancer in UC patients [35]. Although the limited sample size of our cohort impeded a formal analysis, it is worth noting that three out of four patients who developed a hematologic malignancy were being, or had been, treated with azathioprine, which is known to increase the risk of lymphoproliferative disorders [44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…The associations between treatment, surveillance colonoscopy, or disease behavior and carcinogenesis or prognosis have been evaluated using the same data set in other sub-analyses. 6,26,27 Second, the diagnoses of sporadic CRC and CAC in patients with IBD were made at individual institutions and not a central institution, and the diagnoses may not have been standardized. A second review of histological findings was not performed.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the prevalence of primary sclerosing cholangitis, which is one of the cancer risks in those with IBD, was not included in this data set. The associations between treatment, surveillance colonoscopy, or disease behavior and carcinogenesis or prognosis have been evaluated using the same data set in other sub‐analyses 6,26,27 . Second, the diagnoses of sporadic CRC and CAC in patients with IBD were made at individual institutions and not a central institution, and the diagnoses may not have been standardized.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with Crohn's disease (CD) and ulcerative colitis (UC) are more likely to be diagnosed with cancer than the general population (1). Hence, we commend Seishima et al for evaluating the effect of biologics on the risk of advanced-stage inflammatory bowel disease (IBD)-associated intestinal cancer (2). Factors deemed to increase IBD-associated dysplasia have been incorporated into endoscopic guidelines to facilitate a risk-based approach to dysplasia surveillance, albeit with a focus tailored moreso toward UC than CD (3).…”
mentioning
confidence: 99%